The Inheritance Status of Children from Zina Relationship Perspective Complication of Islamic Law and the Civil KUHPidana - Tantri Indar Pratiwi; K. Kurniati; R Abd. Rahman (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
Every child certainly has the same rights in terms of inheritance and others, mistakes made by both parents should not have an impact on children who are victims of immoral acts or adultery of both parents. Every human being has the same rights in the eyes of the law, whether Islamic law or positive law and it is regulated in the law so that in determining the inheritance status of a child born as a result of adultery, if born at the age of marriage of at least 6 (six) months, the child can follow the lineage of the father and the rights to inherit the property. It is also explained in articles 100 and 186 of the Compilation of Islamic Law which means that children from the consequences of adultery have the rights to inherit if they are born in a marital relationship